UPAYA PROMOTIF PREVENTIF KURATIF PADA ANAK DAN REMAJA BERSAMA ORGANISASI PROFESI DI PURWODADI KABUPATEN GROBOGAN - Suwarni, Sri; Saptawati, Tunik; Rini, Tri Diana Puspita; Kristiani, Monica; Azani, Elia; Fajaryanti, Nita (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2025)
Health efforts in the form of promotive, preventive, curative, rehabilitative, and/or palliative measures can be carried out by the government and community self-help groups. Children and adolescents are important assets for shaping a healthy future generation. This service aims to improve the health quality of children and adolescents through promotive, preventive, and curative activities in collaboration with professional organizations in Purwodadi, Grobogan Regency. The methods used were designed as part of the celebration of National Children's Day at Purwodadi City's Green Park on July 27, 2025. The activities included promotive services such as health education on clean and healthy living, balanced nutrition education, and oral health education. Preventive services included free health check-ups, vaccination administration, and health screenings. Meanwhile, curative services include free treatment and vitamin distribution, which provide tangible benefits for children and adolescents in the Purwodadi area. This synergy expands the scope of services and improves the quality of health interventions provided. With 327 participants, this activity successfully increased public knowledge, awareness, and concern about the importance of maintaining health from an early age. The success of this activity is expected to serve as the basis for similar programs in the future, with a focus on sustainability, expansion of the target area, and increased service coverage. This activity is not merely a celebration of National Children's Day but also a collective commitment to building a healthy, intelligent, and competitive younger generation.